2015
DOI: 10.1371/journal.pone.0117315
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 Transcripts in Mononuclear Cells Determine Impaired Graft Function after Kidney Transplantation

Abstract: ObjectiveInterleukin-8 (IL-8) has been associated with ischemia reperfusion injury after renal allograft transplantation. Impaired allograft function may cause major impact on patient morbidity and health care costs. We investigated whether transcript levels in mononuclear cells including IL-8 on the first postoperative day may be involved in immediate allograft dysfunction as defined by reduced relative change in plasma creatinine at the first postoperative day.MethodsWe performed a single center, prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 27 publications
(23 reference statements)
1
19
0
2
Order By: Relevance
“…Borst et al. have shown that reduced levels of IL-8 transcripts in peripheral mononuclear cells predict immediate graft dysfunction and delayed graft function [ 38 ]. In the study by Singh, IL-8 –251AA genotype was associated with 2.7-fold increased risk for allograft rejection in recipients experiencing rejection episodes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Borst et al. have shown that reduced levels of IL-8 transcripts in peripheral mononuclear cells predict immediate graft dysfunction and delayed graft function [ 38 ]. In the study by Singh, IL-8 –251AA genotype was associated with 2.7-fold increased risk for allograft rejection in recipients experiencing rejection episodes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts of MGAT3-AS1, C5aR1, and β-actin were measured with quantitative real-time reverse transcriptase polymerase chain reactions (qRT-PCR). The primers were as follows as previously established 6,16 .…”
Section: Methodsmentioning
confidence: 99%
“…Delayed graft function was defined by at least one dialysis session within 7 days of transplantation 16,18 .…”
Section: Methodsmentioning
confidence: 99%
“…Alterações na expressão gênica demonstraram serem capazes de predizer perdas na função renal (Neuwirt et al, 2014;Borst et al, 2015). Neuwirt e colaboradores identificaram e validaram um painel de três genes (BMP7, THBS1 e TRIB1), cujas expressões em biópsias renais foram capazes de predizer concentrações de creatinina sérica em um período de até 28 meses (Neuwirt et al, 2014).…”
Section: Tabela 4 -Dados Da Eficiência Dos Ensaios De Expressão Mrna unclassified
“…Neuwirt e colaboradores identificaram e validaram um painel de três genes (BMP7, THBS1 e TRIB1), cujas expressões em biópsias renais foram capazes de predizer concentrações de creatinina sérica em um período de até 28 meses (Neuwirt et al, 2014). Já Borst e colaboradores, verificaram que redução na expressão de mRNA do gene da interleucina-18, em células mononucleares do sangue periférico, são capazes de predizer aumento na creatinina sérica e presença de função do enxerto retardada (do inglês delayed graft function), uma forma de falência renal aguda, em até 24h póstransplante (Borst et al, 2015).…”
Section: Tabela 4 -Dados Da Eficiência Dos Ensaios De Expressão Mrna unclassified